Are there political cycles hidden inside government expenditures? - Castro, Vítor (2016)
This article examines the presence of political cycles inside the Portuguese governments’ aggregate expenditures by using annual data for 10 expenditure components. The results indicate that the choice of the expenditure components to be increased during election periods by Portuguese governments generally relates to more visible items such as general public services, social protection and health care.